The Earth-Air Heat Exchanger System Performance Combined with a Solar Collector for Cooling an Indoor Space Room in Medan City - Sitorus, Tulus Burhanuddin; Abda, Syahrul; Ginting Manik, Terang Ukur Hidayat Solihin (International Journal of Integrated Engineering, 2022)
Cooling systems such as ventilation and air conditioning in rooms, offices, and homes have become one of today’s most significant energy consumption aspects. Therefore, to reduce energy consumption, it is necessary to save energy. One way to save energy is by creating an alternative cooling system that does not consume electrical energy. One of them is the cooling system for the earth-air heat exchanger (EAHE). The research objective was to determine the EAHE system’s performance combined with a solar collector for cooling a room in Medan city. The testing room has dimensions of 200 cm x 200 cm x 200 cm. It is testing using a flat plate type solar collector to help air movement by taking advantage of air temperature differences. The testing process starts at 08.00 WIB to 17.00 WIB for several days. The measurement results show that various weather conditions include solar radiation intensity, ambient temperature, and air humidity. During the test, the solar radiation intensity ranged from 62.71-893.43 W/m2, the variation in ambient temperature from 24.65-35.26oC, and the average air humidity 69.80%. The experimental data showed that indoor air temperature fluctuation ranged from 23.01oC to 31.84oC, and the average room temperature was 27.71oC. This study resulted in an average effectiveness value of the EAHE system of 51.56%.